Religion Identity And Political Polarization: How Does Labeling Make It Worst? - Hayat, Nahrul; Nurhakki, Nurhakki (Palita: Journal of Social Religion Research, 2022)
Prabowo's joining of President Jokowi's cabinet is expected to end the polarization of tadpoles versus "kampret". But now, a new label appears called 'Kadrun' or Lizard of the Desert form. Political commentators often use Kadrun on social media as a unique nickname for parties or people against the government. This paper aims to describe the situation of political polarization in Indonesia with the use of religious identity. The analysis focuses on the traces of political labelling "kadrun" on social media that amplify political polarization. The approach used is the descriptive qualitative semiotic framework of Roland Barthes and the concept of labelling as political communication propaganda. The results showed that labelling techniques were used as political propaganda. Kadrun was originally political labelling about the religious identity of certain groups with a political position as opposed to the government. The use of the term kadrun vs cebong on social media by many political commentators has further widened political polarization